(untitled) (Південний архів (історичні науки), 2022)
Purpose. The study of socio-economic development of the South of modern Ukraine requires a comprehensive analysis of the role of different national groups in the development of various sectors of economic activity. Given the predominantly agricultural form of activity of most settlements, it is advisable to analyze the influence of the Jewish population as a catalyst for private and economic development of the peasantry of Odessa district. Analysis of farm development is an important aspect in the study of the general economic situation in the region. The study of the activities of Jewish communities in the towns and villages of Odessa district in the outlined issue is an important aspect in its detailed coverage. One of the aspects of the activities of these communities is the concentration in settlements with a predominantly Jewish population, in the second half of the nineteenth century, the main outlets for the purchase and resale of commodity grain and related goods. Types and varieties of goods are outlined, determined the number of specific goods whose sales were concentrated in the hands of the Jews. The participation of the Jewish community in the socio-economic development of the county and the peculiarities of their involvement in the economic activities of Ukrainian and German settlements have been studied. In addition, the article covers such aspects of the existence of Jewish communities in the county as the main creditors and conditions of their loans to peasants and the situation of Jews during the difficult political and social situation during the anti-Jewish pogroms of the 80’s in the Russian Empire. The analysis of statistical works and available archival sources on the subject of the research will allow to cover in detail the situation of the population in the outlined period. Methods. The study is based on source studies methods for identifying, analyzing and evaluating sources. Methods of historical research are used, in particular historical-comparative, which were used to establish the range of statistical sources needed to cover the topic. Results. The study of the peculiarities of the development of Jewish communities that existed in the South of Ukraine as part of the settlements of the studied county, allows us to conclude about their active economic activity, which in turn encouraged economic activity neighboring German and Ukrainian populations. The analysis of statistical data collected by the Odessa County Administration allowed us to analyze the main aspects of local Judaism, both in the main economic areas in general and in the context of the development of the four largest Jewish communities in the county. The article covers such an aspect of the activities of Jewish communities as lending to the population. The data presented in the article allow us to trace the specifics of the formation and development of Jewish communities in the settlements of the county, changes in the main occupations in their communities. The aspect of counteraction to the local administration’s attempts at pogroms in the settlements where Jews lived is highlighted. Conclusions. The economic and social aspects of the existence of Jewish communities in the territory of Odessa County are analyzed.